APPROACHES AND DISTINCTIONS IN RHETORICAL STRATEGIES BETWEEN GENDERS PORTRAYED IN AN ARTISTIC DEPICTION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article explores the diverse rhetorical tactics utilized by male and female figures in artistic portrayals. By analyzing the gender-specific communication styles and behaviors depicted in visual art, the research endeavors to clarify the distinctions in rhetorical methodologies between genders. Through the scrutiny of a wide array of artworks, this study illuminates the depiction of gendered rhetoric in visual arts and its significance in comprehending gender dynamics in communication